Health-related quality-of-life results from the open-label, randomized, phase III ASPIRE trial evaluating carfilzomib, lenalidomide, and dexamethasone versus lenalidomide and dexamethasone in patientswith relapsed multiple myeloma - Stewart, A.K.; Dimopoulos, M.A.; Masszi, T.; Špička, I.; Oriol, A.; Hájek, R.; Rosiñol, L.; Siegel, D.S.; Niesvizky, R.; Jakubowiak, A.J.; San-Miguel, J.F.; Ludwig, H.; et al. (Journal of Clinical Oncology, 2016)
Purpose To determine the effects of carfilzomib, lenalidomide, and dexamethasone (KRd) versus lenalidomide and dexamethasone (Rd) on health-related quality of life (HR-QoL) in the Carfilzomib, Lenalidomide, and Dexamethasone Versus Lenalidomide and Dexamethasone for the Treatment of Patients With Relapsed Multiple Myeloma (ASPIRE) trial. Methods Patients with relapsed multiple myeloma were randomly assigned to receive KRd or Rd. The European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire C30 and myeloma-specific module were administered at baseline; day 1 of cycles 3, 6, 12, and 18; and after treatment. The Global Health Status/Quality of Life (GHS/QoL) scale and seven subscales (fatigue, nausea and vomiting, pain, physical functioning, role functioning, disease symptoms, and adverse effects of treatment) were compared between groups using a mixed model for repeated measures. The percentages of responders with ≥ 5- or 15-point GHS/QoL improvement at each cycle were compared between groups. Results Baseline questionnaire compliance was excellent (94.1% of randomly assigned patients). KRd patients had higher GHS/QoL scores versus Rd patients over 18 treatment cycles (two-sided P<.001). The minimal important difference was met at cycle 12 (5.6 points) and approached at cycle 18 (4.8 points). There was no difference between groups for the other prespecified subscales from ASPIRE. A higher proportion of KRd patients met the GHS/QoL responder definition (≥ 5-point improvement) with statistical differences at cycle 12 (KRd v Rd patients, 25.5% v 17.4%, respectively) and 18 (KRd v Rd patients, 24.2% v 12.9%, respectively). Conclusion KRd improves GHS/QoL without negatively affecting patient-reported symptoms when compared with Rd. These data further support the benefit of KRd in patients with relapsed multiple myeloma. © 2016 by American Society of Clinical Oncology.